Impact of data availability and pseudo‐measurement synthesis on distribution system state estimation. Issue 1 (13th January 2021) - Zufferey, Thierry; Hug, Gabriela
Abstract: The influence of the advanced metering infrastructure (AMI) set‐up and of the related modelling of pseudo‐measurements on the accuracy of state estimation (SE) in distribution grids, especially at the low‐voltage level, is studied herein. A comprehensive sensitivity analysis is carried out that accounts for the type, the penetration level, and the placement of the metering devices that compose state‐of‐the‐art AMIs. Special care is given to the synthesis of active and reactive power pseudo‐measurements, which substantially impacts the estimation of peak values. Although crucial for system operators, peak values are very often neglected in the SE literature. For that purpose, this study promotes realistic approaches to generate synthetic load profiles and relies on evaluation metrics that are not purely based on the point‐wise precision but consider the statistical properties of the SE outcomes. This is tested on an actual 971‐bus distribution grid with the corresponding smart meter data and is evaluated with respect to the accuracy of active and reactive power injections, bus voltages, and line loadings.